2006
DOI: 10.1021/ol062501g
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodifferentiating Photocyclodimerization of 2-Anthracenecarboxylic Acid Using a Chiral N-(2-Hydroxymethyl-4- pyrrolidinyl)benzamide Template

Abstract: [Structure: see text] Supramolecular enantiodifferentiating photocyclodimerization of 2-anthracenecarboxylic acid (AC) was performed in the presence of (2S,4S)-4-amino-5-chloro-2-methoxy-N-(1-ethyl-2-hydroxymethyl-4-pyrrolidinyl)benzamide (TKS159), and its stereoisomers were employed as chiral templates. The TKS template provides us with a novel hydrogen-bonding and shielding motif for enantioface-selectively binding an AC molecule. Chiral products 2 and 3 were obtained in good enantiomeric excesses (ee's) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…The kinetics as well as the stereo-and regioselectivities [28] of the photodimerizations of these guests mediated by the g-CD derivatives will be investigated in our future works. It was found that these g-CD derivatives showed much higher solubilization abilities for aromatic guests than native CDs or other frequently used derivatives such as hydroxypropyl-b-CD.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics as well as the stereo-and regioselectivities [28] of the photodimerizations of these guests mediated by the g-CD derivatives will be investigated in our future works. It was found that these g-CD derivatives showed much higher solubilization abilities for aromatic guests than native CDs or other frequently used derivatives such as hydroxypropyl-b-CD.…”
Section: Resultsmentioning
confidence: 99%
“…Of the many weak non-covalent interactions, the hydrogen-bonding interaction, which is Brought to you by | MIT Libraries Authenticated Download Date | 5/10/18 6:58 PM strong and directional, is most frequently employed as a tool for capturing the guest substrate and controlling its orientation, configuration and/or conformation in the supramolecular complex formed. [55,56] Multiple hydrogen-bonding interactions provided by chiral templates can also confine and preorganize substrate(s) to drive photoreactions towards the specific stereochemistry desired. [57][58][59] Bach et al have developed a series of Kemp's acidbased chiral templates, such as 32 and 33, which possess a lactam moiety as a hydrogen-bond donor/acceptor, and an aromatic moiety as both a built-in photosensitizer and a fence to shield one of the enantiotopic faces of an amidecarrying prochiral substrate bound to the template.…”
Section: Catalytic Supramolecular Photochirogenesis With Chiral Templmentioning
confidence: 99%
“…2.16 ) forms 1:1 complexes with 15 , affording mixtures of photodimers that are enriched in the anti HT products, with ee ' s of 10 -30% (up to 40% at − 50 ° C). 80 Similarly, the chiral shield 11 developed by Bach blocks one of the two prochiral faces of a bound pyridone molecule to direct its ensuing [4 + 4] photocycloaddition to cyclopentadiene. The reaction is characterized by high conversion to a 2:3 mixture of the endo and exo products, both of which are obtained with high ee ' s ( Fig.…”
Section: Templated (4 π + 4 π ) Photocyclization Reactions In Solutionmentioning
confidence: 99%
“…Chiral shields 11 and 16 bind anthracene -2 -carboxylic acid and pyridone, respectively, furnishing stereoselectivity in the ensuing photocyclization reactions 80,84. …”
mentioning
confidence: 99%